THE EFFORT ANALYSIS AFRICAN CATFISH BREEDING IN TARPAULIN POOLAT HANGTUAH VILLAGE PERHENTIAN RAJA SUB DISTRICT KAMPAR DISTRICT RIAU PROVINCE - M. ARIE AFFANDI; Eni Yulinda; HENDRIK ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The aim of this research was to know the condition of african catfishbreeding in tarpaulin pool at hangtuah village and the development possibilities inthe future discussed on the financial side, and also to know the proper level ofAfrican catfish breeding effort at hangtuah village.The applied method in this research was survey method. Respondents inthis research is farmers who do breeding the African catfish in tarpaulin pool athangtuah village, where the populations is 330 people and the number ofrespondents who where taken as much as 5% of the total populations of thefarmers as many as 16 respondents. Taking as much as 5% of respondents dobecause the majority of populations at hangtuah village have the same job(homogen).The average of stated financial used by the farmers at hangtuah villagewas Rp. 4.239.375,00 per month. The average of total cost used was Rp.2.450.895,00 per month. The profit range got by the farmers was Rp.1.788.479,6,00 per month. BCR values were 1,84 for this fish breeding. It meantthat this breeding effort deserve to be continued cause the BCR values >1,meanwhile the PPC values range at 5,02.Keyword: African catfish, tarpaulin pool, hangtuah village